Acceptability of a Dyadic Psychoeducational Intervention for Patients and Caregivers - Titler, Marita G. (Oncol Nurs Forum, 2020)
PURPOSE: To assess participants’ acceptability of the FOCUS program, a psychoeducational intervention, delivered to multiple patient–caregiver dyads in a small-group format. PARTICIPANTS & SETTING: A total of 72 adults diagnosed with cancer and their caregivers (36 dyads) who participated in 1 of 11 FOCUS programs delivered at two Cancer Support Community affiliates. METHODOLOGIC APPROACH: A pre-/postintervention design was used to implement the FOCUS program. The FOCUS Satisfaction Instrument measured participants’ satisfaction with the program, usefulness of the materials, helpfulness in coping with cancer, duplication of services, willingness to recommend the program to others, and the most and least beneficial aspects. Descriptive statistics, t tests, and content analysis were used. FINDINGS: Most participants reported that the program did not duplicate services, that it helped them cope with cancer, and that they would recommend the program to others. The most beneficial aspects of the program were the group format and the dyadic approach. IMPLICATIONS FOR NURSING: A group format and dyadic approach to address the psychosocial impact of cancer is highly valued by individuals with cancer and their caregivers. Nurses are well positioned to lead implementation of programs like the FOCUS program that complement other cancer support services.